Potential of Bacillus spp. Consortium for controlling Meloidogyne spp. and enhancing tomato crop production - Yulmira Yanti; Winarto; Hasmiandy Hamid; Pandu Chayadi Wasirin (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: rhizobacteria Bacillus spp. are microorganisms that reside in plant roots that function as biocontrol agents of plant diseases and increase plant growth and yield. Bacillus spp. consortium is a combination of several Bacillus spp. that synergize and do not inhibit each other. The study aimed to obtain the best Bacillus spp. consortium to control Meloidogyne spp. and increase the growth and yield of tomato plants. Methods: This research is experimental using a completely randomized design consisting of 2 stages, namely 1.) Compatibility test of rhizobakteria consortium Bacillus spp. consists of 6 treatments 4 replicates and 2.) Test consortium rhizobakteria Bacillus spp. selected to control Meloidogyne spp. and increase the yield of tomato plants. The observed variables were the development of root swelling by Meloidogyne spp., and the growth of seedling, vegetative, and generative phases. Results: The results showed that testing all isolates of rhizobacteria Bacillus spp. showed compatibility (compatible). Bacillus spp. rhizobacteria consortium can suppress the development of Meloidogyne spp. and showed different results compared to the control. Bacillus spp. rhizobacteria consortium can increase the growth of tomato seedlings and showed different results compared to the control. Bacillus spp. rhizobacteria consortium can increase the growth of tomato plants in the vegetative phase and showed different results compared to the control. rhizobacteria consortium Bacillus spp. can increase the growth of tomato plants in the vegetative phase and shows different results compared to the control. Conclusion: The best rhizobakteria Bacillus spp. consortium in suppressing the development of Meloidogyne spp. and increasing the growth and yield of tomato plants is Bacillus cereus strain RBI2AB2.2 + Bacillus cereus strain RBIKDA2.2.